The Effect of the Accumulated Dust in the Vital Systems and the Population in the Environment of Basra Governorate - ناصر عبدالله الصرايفي علي (Journal of College of Education, 2021)
Preserving the environment and vital systems is essential. The current study sheds light on the levels of dust falling over Basra Governorate by monitoring the amount of dust, indicating its type, knowing the chemical compounds and heavy elements from which the dust is composed of and as well as knowing the size of the atom. The results of the study showed that the dust falling over Basra Governorate consisted of minerals (calcite, quartz, gypsum, dolomite, feldspar, and kaolin). Calcite and quartz were recorded in all the seasons and the studied sites, while there was a discrepancy for the rest of the minerals between the parts of the study area. Dust particles appeared in different shapes, showing the sharp-pointed cylindrical shape, the rectangular shape with sharp heads, and the circular shape as well as the salt shapes. Dust particles are characterized by being infinitesimally small, as their sizes ranged between (14,876 - 56,812) nanometers, and thus they can turn into trapped dust, which carries between its folds various types of toxic and carcinogenic heavy elements. About (16) heavy elements (Zr, Zn, Sn) have been studied. (, Se, S, Pb, Ni, Mn, Hg, Fe, Cu, Co, Cr, Cd, As, Al) all exceeded the permissible environmental limit, hence these particles have mechanical effects on the natural barrier of the human respiratory system; moreover, they can infect various Other diseases such as eye, skin and ear diseases.